2017
DOI: 10.1016/j.jvs.2016.05.093
|View full text |Cite
|
Sign up to set email alerts
|

A potential contribution of dipeptidyl peptidase-4 by the mediation of monocyte differentiation in the development and progression of abdominal aortic aneurysms

Abstract: Increased plasma DPP-4 activity may correlate with aneurysmal development. CD26 on monocytes plays a critical role in cell differentiation, possibly mediated by extracellular signal-regulated protein kinase 1/2-p21 axis signaling pathways and cytoskeletal proteins reassembly. Exploring the role of DPP-4 further may yield potential therapeutic insights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
0
20
1
Order By: Relevance
“…Krizhanovskii et al showed increased GLP1 in plasma of patients with dilatation of the ascending aorta, which could imply a decreased DPP-4 activity, and other studies have found a decreased DPP-4 activity in the plasma of patients with chronic obstructive pulmonary disease, a disease that has been linked to AAA rupture [40][41][42]. However, Lu et al detected a significant increase in DPP-4 in plasma from patients with AAA compared with the control group [16]. This discrepancy cannot be fully explained but our groups of study subjects differ, where Lu et al had a younger group of controls compared to the AAA patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Krizhanovskii et al showed increased GLP1 in plasma of patients with dilatation of the ascending aorta, which could imply a decreased DPP-4 activity, and other studies have found a decreased DPP-4 activity in the plasma of patients with chronic obstructive pulmonary disease, a disease that has been linked to AAA rupture [40][41][42]. However, Lu et al detected a significant increase in DPP-4 in plasma from patients with AAA compared with the control group [16]. This discrepancy cannot be fully explained but our groups of study subjects differ, where Lu et al had a younger group of controls compared to the AAA patients.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, favourable effects of both DPP4 inhibition and GLP-1 on AAA development and progression have been reported for animal models [13][14][15][16][17][18]. However, there are no reports showing the expression and activity of DPP4 in human aneurysm tissue.…”
Section: Introductionmentioning
confidence: 99%
“…58 DPP4 inhibitors work by augmenting the incretin effect. Lu et al 59 have shown a positive correlation between the relative intensity of plasma DPP4 and AAA diameter (p < 0.05) which may be mediated through an action of DPP4 on monocyte-macrophage differentiation. Using the DPP4 inhibitor alogliptin, Bao et al were able to attenuate aneurysm formation in a dose-dependent fashion (p < 0.02) using rodent models of AAA (intraluminal elastase and extraluminal calcium chloride).…”
Section: Oral Hypoglycaemic Agentsmentioning
confidence: 94%
“…Furthermore, they found that alogliptin treatment was associated with lower tissue levels of MMP-2 (p < 0.001), MMP-9 (p < 0.001) and reactive oxygen species (p < 0.0001) and preservation of mural elastin. 59 Kohashi et al 60 performed a similar study using the DPP inhibitor MK0626 in an ApoE-deficient AngII mouse model and found that treatment with MK0626, but not treatment with native incretins GIP-1 or GLP-1, was associated with a 30% reduction in aneurysm formation, significantly less IL-1β expression and an increased ratio of tissue inhibitor of metalloproteinase (TIMP)-2 to MMP-9. MK0626 did not affect aortic IL-6 or TNF-α expression in this study.…”
Section: Oral Hypoglycaemic Agentsmentioning
confidence: 99%
“…Two studies matched cases and controls for age (33,34) and sex (32,34). Three studies reported that controls were healthy (30,32,34). A case-control study reported that plasma DPP-4 enzyme activity was significantly increased in both large and small AAA patients compared to controls and positively correlated with AAA diameter (32) ( Table 3A).…”
Section: Evidence From Human Studies For a Role Adipokines And Pvat Imentioning
confidence: 99%